1998
DOI: 10.1016/s0042-6989(97)00238-1
|View full text |Cite
|
Sign up to set email alerts
|

Constraints on long range interactions mediating contour detection

Abstract: Contour detection may be mediated by lateral interactions between neighboring cortical neurons whose receptive fields have collinear axes of preferred orientation. This hypothesis was tested in psychophysical experiments and computer simulations using a contour detection task in which observers searched for groups of Gabor patches that followed spatially extended contour paths embedded in noise consisting of several hundred Gabor patches with random positions and orientations. The orientation-selective units i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
116
1
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 118 publications
(126 citation statements)
references
References 29 publications
8
116
1
1
Order By: Relevance
“…tal results (Kovacs & Julesz, 1993;Pettet et al, 1998). In particular, Kovacs and Julesz (1993) reported that the critical separation for closed contours is about two times larger than for open contours (for elements of relatively high spatial frequency, 8.3 cpd).…”
Section: Open Vs Closed Contoursmentioning
confidence: 93%
See 1 more Smart Citation
“…tal results (Kovacs & Julesz, 1993;Pettet et al, 1998). In particular, Kovacs and Julesz (1993) reported that the critical separation for closed contours is about two times larger than for open contours (for elements of relatively high spatial frequency, 8.3 cpd).…”
Section: Open Vs Closed Contoursmentioning
confidence: 93%
“…In particular, Kovacs and Julesz (1993) reported that the critical separation for closed contours is about two times larger than for open contours (for elements of relatively high spatial frequency, 8.3 cpd). However, in these previous experiments the relative density between contour and background elements was changed across conditions, with either the spacing between contour elements varied and the spacing between background elements fixed (Kovacs & Julesz, 1993), or the spacing between contour elements fixed and the number of background elements varied (Pettet et al, 1998). The combination of the local density cue present in their stimuli and contour closure could thus explain the facilitation reported for the detection of closed contours.…”
Section: Open Vs Closed Contoursmentioning
confidence: 93%
“…Two categories were motivated by the information commonly used by existing texture features: 2nd-order statistics, and short-range higher order statistics (HOS) (typically obtained from image patches). The use of the third category, contour data, was motivated by the fact that the human visual system is extremely adept at exploiting these visual cues [25], [44], [46][47], [53] and that they utilise long-range HOS. We conducted an experiment with human observers that showed that for the Pertex database [29], contours are the most useful category of data for human texture discrimination.…”
Section: Discussionmentioning
confidence: 99%
“…These images are outlined using the above colour scheme to indicate which property is most important to their recognition: contour maps (red), 2nd-order statistics contained in phase-randomised images (blue) or the short-range interactions contained in randomised blocked images (cyan). [46][47]. In addition, it has been shown that objects can be identified using discontinuous fragmented contour segments [44].…”
Section: ) Dividing a Contour Into Segmentsmentioning
confidence: 99%
See 1 more Smart Citation